Pemetaan Kajian Tafsir Periode Sahabat dan Tâbi‘în - suryanto, Suryanto (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2012)
The study of the Koran is always evolving since it revealed. The emergence of the various books of commentary which is loaded with various methods and approaches, is clear evidence that efforts to interpret the Koran was never stopped, and that the Muslims intend to make it as a dialogue partner in life and to develop a civilization. In each period, interpretation has its own peculiarities and characteristics. Between one period to another can not be forced together. Related to the issue, this paper presents the mapping of classical interpretation studies whose focuses on “the characteristics and uniqueness of this interpretation.” The interpretation of the Koran in classical period has not revealed in a specific form, both al-ma’thûr or al-ra’y. The interpretation process of this period is still common al-ma’thûr when it viewed in terms of sources and forms of interpretation. Commentators seem clearly given the interpretation together in one package, along with the people coaching personality, which related to faith, moral, and jurisprudence. The interpretation is applied integrally not partially, which included other fields, such as theology, jurisprudence, and mysticism. This method then indicates the other, called today by the ijmâlî